Pid-Based Bottle Shark Heart Heater Design and Development - Muda Irwandy; Asran Asran; Kartika Munir; Salahuddin Salahuddin (International Journal of Engineering, Science and Information Technology, 2023)
Traditional medicines are ingredients or ingredients in the form of plant ingredients, animal ingredients, mineral ingredients, galenic preparations, or mixtures of these materials, which have been used for generations for treatment and can be applied according to the norms in force in society. Bottle shark (Centrophorus atromarginatus) has good prospects as a producer of liver oil; this fish is easy to catch and occurs in relatively large quantities in Indonesian waters. The catch rate until now is only 39% of its sustainable potential. Bottled shark liver oil contains 90% squalene, Vitamin A, and Omega, which are very useful for the human body as a supplement for heart disease and stomach ulcers and increase stamina and brain intelligence. The rapid Development of technology certainly benefits the people who use it. One example of today's use of technology is applying a technology system for the fisheries sector. This tool works automatically to monitor the processing of bottled shark livers. That way, fishermen don't have to worry about cloudy weather or things that will take longer than processing the shark liver bottle. This Bottle Shark Liver Heater uses temperatures at 31˚, 32˚, 33˚, 34˚, and 35˚. With PID (Proportional Integral Derivative) control, the quality of the Bottle Shark liver can be maintained. This tool is supported by a DS18B20 temperature sensor, Arduino uno, Relay, Ceramic Heater element, DC Fan, LCD 16X12, Power Supply, and Switch. It is hoped that the community, with this automatic system device, can make it easier to manage Bottle Shark Liver Oil.